List of Articles in Periodicals Relating to the Problem of Hungary - Héderváry, Claire de (1960)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. A list of the most important articles published in the English (American), French, German and Italian press on Hungary between October 1956 and July 1960.